RAS70 peptide targets multiforme glioblastoma by binding to the plasma membrane heat shock protein HSP70 - Shevtsov, Maxim; Yudintceva, Natalia; Bobkov, Danila; Likhomanova, Ruslana; Nechaeva, Anastasiya; Mikhailova, Elena; Oganesyan, Elena; Fedorov, Viacheslav; Kurkin, Andrey; Lukacheva, Anastasiya; Fofanov, Georgii; Kim, Aleksander; et al. (Frontiers in Oncology, 2025)
Multiforme glioblastoma-homing peptides, particularly targeting plasma membrane-bound heat shock protein mHsp70, demonstrate great application potential for tumor theranostics. In the current study, to further increase the bioavailability as well as penetration capacity through the blood-brain barrier (BBB) of the mHsp70-targeted peptide TKDNNLLGRFELSG, which is known to bind to the oligomerization sequence of mHsp70 chaperone, the latter was conjugated with tripeptide RGD (forming chimeric peptide termed RAS70). In the model BBB system RAS70 efficiently crossed the barrier accumulating in the glioblastoma cells. Subsequently, in the orthotopic glioma models, intravenous administration of the fluorescently labeled agent (RAS70-sCy7.5) resulted in the tumor retention of peptide (further confirmed by histological studies). Thus, as shown by the biodistribution studies employing epifluorescence imaging, accumulation of RAS70-sCy7.5 in C6 glioma was significantly enhanced as compared to scramble peptide. Local application of the RAS70-sCy7.5 peptide that was sprayed over the dissected brain tissues helped to efficiently delineate the tumors in glioma-bearing animals employing an intraoperative fluorescent imaging system. Tumor-specific internalization of the peptide was further confirmed on the ex vivo primary GBM samples obtained from adult neurooncological patients. In conclusion, RAS70 peptide demonstrated high glioma-homing properties which could be employed for the intraoperative tumor visualization as well as for developing a potential carrier for drug delivery.